Pengaruh Direct Marketing Dan Digital Marketing, Terhadap Keputusan Pembelian (Studi Kasus Usaha Spare Part Pada Cikal Motor Bandar Lampung) - Hakim, Muhtar; Rahayu, Sri Retnaning (Jurnal Manajemen DIVERSIFIKASI, 2022)
Product marketing is one of the keys to maximizing business objectives in generating profits. There are two types of marketing, direct marketing and digital marketing in an effort to influence consumer decisions. Direct marketing and digital marketing are carried out to introduce and promote products as one of the marketing strategies. The purpose of this study was to analyze the effect of direct marketing and digital marketing on purchasing decisions. The research design is quantitative research. The method is descriptive quantitative method. The objects research are direct marketing, digital marketing, and purchasing decisions. This research activity at Cikal Motor Bandar Lampung. The research population is the customers of Cikal Motor Bandar Lampung with samples 96 respondents. Data collection techniques using questionnaires. The analytical tool used is data quality analysis and multiple linear regression analysis with SPSS program. The results of the study show that partially direct marketing and digital marketing have a positive and significant effect on purchasing decisions. Simultaneously direct marketing and digital marketing together have an influence on the purchasing decisions.